Видатки бюджетів територіальних громад як стимули соціально-економічного розвитку регіонів - Мащенко, Ольга Вікторівна; Білик, Юлія Сергіївна (Чорноморський національний університет імені Петра Могили ТОВ "ДКС Центр", 2025)
У статті досліджено механізм формування видаткової частини бюджетів територіальних гро мад. Визначено особливості утворення видатків територіальних громад. Розглянуто та проаналізовано склад, структуру та динаміку видаткової частини міських бюджетів територіальних громад Харківської області за 2021—2024 роки. Проведено оцінку видатків бюджетів і з'ясовано основні виклики та фінансові можливості розвитку територіальних громад Харківської області. Виявлено основні проблеми та недоліки при здійсненні бюджетного забезпечення соціально-економічного розвитку територій. Визначено основні фактори впливу на перерозподіл бюджетних ресурсів. Обгрунтовано необхідність посилення контролю за ефективністю використання бюджетних коштів для забезпечення безперебійного фінансування життєво важливих сфер. Наголошено на важливості своєчасного коригування бюджетних програм з урахуванням динамічних змін економічної ситуації та потреб населення у період воєнного стану.

Analysis of the structure and dynamics of expenditures of territorial communities of the Kharkiv region for 2021—2024 allows us to identify the main trends of local fiscal policy in the context of martial law and economic crisis. Summarizing the data by major categories of expenditures allows for a comprehensive view of funding priorities and potential risks in the context of sustainable community development. This article presents a detailed analysis of expenditure management in the Kharkiv region's territorial communities during the martial law period. The key factors influencing the redistribution of budgetary resources are identified, including a decline in local tax revenues due to the suspension of entrepreneurial activity and the destruction of infrastructure. Changes in the structure of local budget expenditures are generalized, focusing on funding measures to strengthen defense capabilities and provide humanitarian assistance to the population. The study analyzes structural shifts in the expenditure part of local budgets, which made it possible to identify trends and specific changes in the funding priorities of territorial communities. The impact of hostilities on the budgetary obligations of communities is analyzed, revealing the necessity to optimize expenditures and reallocate funds towards critical areas-housing and utilities, healthcare, and social protection. The need to strengthen control over public spending efficiency is substantiated to ensure uninterrupted financing of vital sectors. Emphasis is placed on the timely adjustment of budget programs in response to dynamic changes in the economic environment and the population's needs during wartime. This approach helps maintain funding stability in key sectors and ensures the viability of communities in times of crisis. Additionally, ensuring transparency in using budget funds is highlighted, as this contributes to increasing public trust in local self-government bodies and strengthens financial discipline.
Budget expenditures of territorial communities as incentives for the socio-economic development of regions
Keywords: видатки громади; бюджет територіальної громади; фінансове забезпечення; трансферти; субвенції; децентралізація; community expenditures; territorial community budget; financial support; transfers; subventions; decentralization